2015
DOI: 10.3892/mmr.2015.4493
|View full text |Cite
|
Sign up to set email alerts
|

Triptolide reverses the Taxol resistance of lung adenocarcinoma by inhibiting the NF-κB signaling pathway and the expression of NF-κB-regulated drug-resistant genes

Abstract: Paclitaxel (or Taxol®) is a first-line chemotherapeutic drug for the treatment of non-small cell lung cancer; however, resistance to the drug is an important factor, which influences the outcome of chemotherapy. The present study aimed to investigate the role of triptolide (TPL) in reversing Taxol-resistant human lung adenocarcinoma and to elucidate the underlying molecular mechanism of resistance reversal mediated by TPL. It was hypothesized that this experimental approach would assist in solving the problem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 23 publications
3
33
0
Order By: Relevance
“…The change in cell viability was confirmed via flow cytometry assay, and morphology variation was observed by fluorescent staining with Hoechst 33258 and Annexin V-FITC/PI, consistent with previous reports (25). Much research has focused on the ability of TPI to inhibit proliferation and migration of tumors, and its potential applications in drug resistance and radiation/chemotherapy sensitization (26). The anti-cancer mechanisms of TPI have been shown to be related to multiple signals and pathways, including the estrogen receptor signaling pathway (25) and phospholipase D1 expression (27).…”
Section: Discussionsupporting
confidence: 87%
“…The change in cell viability was confirmed via flow cytometry assay, and morphology variation was observed by fluorescent staining with Hoechst 33258 and Annexin V-FITC/PI, consistent with previous reports (25). Much research has focused on the ability of TPI to inhibit proliferation and migration of tumors, and its potential applications in drug resistance and radiation/chemotherapy sensitization (26). The anti-cancer mechanisms of TPI have been shown to be related to multiple signals and pathways, including the estrogen receptor signaling pathway (25) and phospholipase D1 expression (27).…”
Section: Discussionsupporting
confidence: 87%
“…Triptolide exerts potent anti-cancer effects in several cancer types including lung cancer [10], liver cancer [11], pancreatic cancer [12], and colon cancer [13]. In our present study, we demonstrated that triptolide exhibited promising anti-cancer potential in human gastric BGC-823 cells.…”
Section: Discussionsupporting
confidence: 61%
“…Our results showed that toxic effects were increased in BGC-823 cells by triptolide treatment (10,20, and 40 nM) in a dosedependent manner (Figure 2). …”
Section: Triptolide Induced Cell Cytotoxicity In Human Gastric Cancermentioning
confidence: 63%
See 2 more Smart Citations